Establishing Australian Norms for the Jebsen Taylor Test of Hand Function in Typically Developing Children Aged Five to 10 Years: A Pilot Study - Beagley, S.; Reedman, S.; Sakzewski, L.; Boyd, Roslyn (2015)
© 2015 Taylor & Francis Group, LLC Aims: The aim of this study was to present preliminary normative data for the Jebsen Taylor Test of Hand Function test (JTTHF) in Australian children. Normative data provide reference values for comparison of upper limb capacity when evaluating and planning treatment. Methods: The JTTHF administration procedures and materials were standardized. One hundred and two typically developing children aged 5 to 10 years in Brisbane, Australia, were then assessed using the JTTHF. Results: Five-year-old children were significantly different to all other groups (one year age bands), and 6-year-old children were significantly different from 9-year-old children in the dominant hand. Regression modeling showed improvements of 0.9 and 0.89 s in JTTHF total time for the dominant and nondominant hands, respectively, for every 12 months of maturation in 6- to 10-year-old children. Conclusions: This paper presents preliminary JTTHF norms for Australian typically developing children 5 years, 6 to 7 years, 8 to 9 years, and 10 years of age.